STOREVAL, un indicateur de valeur écologique du foncier pour la définition de meilleures stratégies de gestion des sites des entreprises en lien avec les réseaux écologiques locaux - Laura Thuillier; Caroline De Zutter; Denis Leca; Nathalie Machon (VertigO, 2022)
Industrial companies, because of the land ownership of their production sites and the products they use, contribute to the degradation and fragmentation of natural habitats, negatively impacting biodiversity. They are subject to increasing societal pressure to reduce their impacts. Thus, more and more companies are developing strategies to take biodiversity into account in their activities. They are establishing partnerships with recognized scientific organizations in order to study their impacts on biodiversity and propose measures to reduce them. In this article, we present an ecological value indicator, Storeval, which is the result of this type of partnership. Based on biodiversity inventories, structural indicators and ecological network modelling, this composite indicator allows to estimate the quality of the ecosystem, the pressures exerted on it, to prioritize management measures and to evaluate their effects over time. It is applicable at the very fine scale of the habitat patch for sites composed of plots more or less dispersed in space. On sites where it has been used, Storeval has served as a basis for establishing long-term management plans. At the company level, it appears to be a tool for driving change towards practices that are more respectful of biodiversity.